2021
DOI: 10.3390/cells10071733
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Multiple Sclerosis: Role in the Pathogenesis and Potential Usefulness as Biomarkers and Therapeutic Tools

Abstract: Although extracellular vesicles (EVs) were initially relegated to a waste disposal role, nowadays, they have gained multiple fundamental functions working as messengers in intercellular communication as well as exerting active roles in physiological and pathological processes. Accumulating evidence proves the involvement of EVs in many diseases, including those of the central nervous system (CNS), such as multiple sclerosis (MS). Indeed, these membrane-bound particles, produced in any type of cell, carry and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 113 publications
(142 reference statements)
0
22
0
1
Order By: Relevance
“…Bestowing this reason, EVs attract special space for acting both as diagnostic markers and therapeutics in neurodegenerative diseases. The majority of studies observed the role of EVs in both diagnostics and therapeutics ( Candelario and Steindler, 2014 ; Jan et al, 2017 ; Lee and Kim, 2017 ; Izadpanah et al, 2018 ; Hill, 2019 ; Jiang et al, 2019 ; You and Ikezu, 2019 ; Yuan et al, 2019 ; Zhang et al, 2019 , 2021 ; Abdel-Haq, 2020 ; Kapogiannis, 2020 ; Mäger et al, 2020 ; Shaimardanova et al, 2020 ; Vassileff et al, 2020 ; Yin et al, 2020 ; Anakor et al, 2021 ; Cui et al, 2021 ; D’Anca et al, 2021 ; Gagliardi et al, 2021 ; He et al, 2021 ; Jin et al, 2021 ; Manu et al, 2021 ; Toshihide, 2021 ; Upadhya and Shetty, 2021 ; Zhao et al, 2021 ; Picca et al, 2022 ). Notably, 19 studies observed the pioneering role of EVs as a diagnostic biomarker in neurodegenerative diseases ( Table 2 ; Coleman and Hill, 2015 ; Thompson et al, 2016 ; Vella et al, 2016 ; Barreca et al, 2017 ; Chen et al, 2017 ; Li et al, 2018 ; Pluta et al, 2018 ; Ramirez et al, 2018 ; Gámez-Valero et al, 2019 ; Karnati et al, 2019 ; Lee et al, 2019 ; Pluta and Ułamek-Kozioł, 2019 ; Pulliam et al, 2019 ; Vinaiphat and Sze, 2019 ; Banack et al, 2020 ; Guedes et al, 2020 ; Hornung et al, 2020 ; Rani et al, 2020 ; Leggio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bestowing this reason, EVs attract special space for acting both as diagnostic markers and therapeutics in neurodegenerative diseases. The majority of studies observed the role of EVs in both diagnostics and therapeutics ( Candelario and Steindler, 2014 ; Jan et al, 2017 ; Lee and Kim, 2017 ; Izadpanah et al, 2018 ; Hill, 2019 ; Jiang et al, 2019 ; You and Ikezu, 2019 ; Yuan et al, 2019 ; Zhang et al, 2019 , 2021 ; Abdel-Haq, 2020 ; Kapogiannis, 2020 ; Mäger et al, 2020 ; Shaimardanova et al, 2020 ; Vassileff et al, 2020 ; Yin et al, 2020 ; Anakor et al, 2021 ; Cui et al, 2021 ; D’Anca et al, 2021 ; Gagliardi et al, 2021 ; He et al, 2021 ; Jin et al, 2021 ; Manu et al, 2021 ; Toshihide, 2021 ; Upadhya and Shetty, 2021 ; Zhao et al, 2021 ; Picca et al, 2022 ). Notably, 19 studies observed the pioneering role of EVs as a diagnostic biomarker in neurodegenerative diseases ( Table 2 ; Coleman and Hill, 2015 ; Thompson et al, 2016 ; Vella et al, 2016 ; Barreca et al, 2017 ; Chen et al, 2017 ; Li et al, 2018 ; Pluta et al, 2018 ; Ramirez et al, 2018 ; Gámez-Valero et al, 2019 ; Karnati et al, 2019 ; Lee et al, 2019 ; Pluta and Ułamek-Kozioł, 2019 ; Pulliam et al, 2019 ; Vinaiphat and Sze, 2019 ; Banack et al, 2020 ; Guedes et al, 2020 ; Hornung et al, 2020 ; Rani et al, 2020 ; Leggio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVs attract special space for acting both as diagnostic markers and therapeutics in neurodegenerative diseases. The majority of studies observed the role of EVs in both diagnostics and therapeutics (Candelario and Steindler, 2014;Jan et al, 2017;Lee and Kim, 2017;Izadpanah et al, 2018;Hill, 2019;Jiang et al, 2019;You and Ikezu, 2019;Yuan et al, 2019;Zhang et al, 2019Zhang et al, , 2021Abdel-Haq, 2020;Kapogiannis, 2020;Mäger et al, 2020;Shaimardanova et al, 2020;Vassileff et al, 2020;Yin et al, 2020;Anakor et al, 2021;Cui et al, 2021;D'Anca et al, 2021;Gagliardi et al, 2021;He et al, 2021;Jin et al, 2021;Manu et al, 2021; 10.3389/fnmol.2022.1061076 Toshihide, 2021; Upadhya and Shetty, 2021;Zhao et al, 2021;Picca et al, 2022). Notably, 19 studies observed the pioneering role of EVs as a diagnostic biomarker in neurodegenerative diseases (Table 2; Coleman and Hill, 2015;Thompson et al, 2016;Vella et al, 2016;Barreca et al, 2017;Chen et al, 2017;Li et al, 2018;Pluta et al, 2018;Ramirez et al, 2018;Gámez-Valero et al, 2019;Karnati et al, 2019;Lee et al, 2019;Pluta and Ułamek-Kozioł, 2019;…”
Section: Diagnosticmentioning
confidence: 99%
“…Detection and characterization of extracellular vesicles might represent, however, a technical challenge [52]. Diagnostic, prognostic, disease, and treatment monitoring values of extracellular vesicles detection, both in CSF and blood, have been proposed for MS [53,54,55,56].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Their particular structure may give details regarding a cell's origin and the their pathological mechanism. 57,58 Papers focusing on CSF-EVs found excellent associations with MS disease activity or disability, suggesting that they might have a role in diagnosis. Due to the intrusive process needed to get CSF samples, CSF-EVs do not fulfil the requirement for a widely accessible marker, making them ineffective for tracking illness progression over time.…”
Section: Human Studymentioning
confidence: 99%
“…EVs in CNS may be seen in peripheral fluids because they can cross the blood–brain barrier (BBB). Their particular structure may give details regarding a cell's origin and the their pathological mechanism 57,58 . Papers focusing on CSF‐EVs found excellent associations with MS disease activity or disability, suggesting that they might have a role in diagnosis.…”
Section: Role Of Exosome As a Biomarker In Msmentioning
confidence: 99%